Emergency department’s patient safety culture perceived by healthcare workers: A scoping review protocol - Min Ji Kim (PLoS ONE, 2025)
A strong patient safety culture is critical for ensuring effective healthcare systems, particularly in high-risk environments such as emergency departments. Assessing patient safety culture requires the identification of strengths and weaknesses within clinical departments to enable targeted improvement. Patient safety in emergency departments is especially vulnerable due to overcrowding, necessity for rapid decision-making, and high pressure. However, the existing literature has not been systematically mapped to understand how healthcare workers perceive the patient safety culture in these settings. This scoping review aims to synthesize and map available evidence on patient safety culture as perceived by healthcare workers in emergency departments. This review will be conducted following the Joanna Briggs Institute methodology designed explicitly for scoping reviews, and the results will be reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews (PRISMA-ScR). The inclusion criteria will be based on the Population (healthcare workers), Concept (patient safety culture), and Context (emergency department settings) framework. A comprehensive search will be conducted in PubMed, CINAHL (EBSCOhost), Web of Science, Embase, Cochrane Library, KISS, and grey literature sources, such as ProQuest Dissertation & Theses Global and Google Scholar. Study selection and data extraction will be performed independently by two researchers, with a third researcher resolving discrepancies. Descriptive analysis will summarize the study characteristics, while content and thematic analyses will identify key themes related to patient safety culture. The findings will be presented at academic conferences and published in a peer-reviewed journal.